Adopting a webct learning environment in lecture based mining engineering education. - Thompson, Roger J.
Two years ago, the Department of Mining Engineering at the University of Pretoria expanded its lecture-based teaching approach to encompass the utilities of a WebCT environment in two of it modules; a core course and a capstone course in surface mining. The aims behind the adoption of the web-supported approach were primarily to improve students' abilities to both acquire (at core level) and apply knowledge ( at capstone level), in the form of problem solving approaches to mining-related issues. Whilst significant differences existed between the course outcomes, it was anticipated that a WebCT environment could be adopted to maximise teaching effectiveness. Specifically electronic notes and practical group field data collation offered a number of additional functionalities unavailable in a conventional lecture-only based program. In particular, realistic illustrations of the use of equipment, operational analysis, dimensionality and dynamic concepts in mining engineering became possible. This paper broadly introduces the curriculum design process in mining engineering, following which the change process of integrating these design principles and teaching functions into a lecture-based teaching program is described. The description of multi media WebCT mining modules is intended to underscore the motivation and incentives required to develop similar modules and to highlights the resources and support required for sustaining such an approach. Finally, based on evidence from student responses to module surveys, the author shows how several aspects of module design at core and capstone level affect student experiences of learning in this environment.
Keywords: Mining engineering -- Study and teaching; WebCT; Mining engineering curriculum